Mycetoma: A critical appraisal of educational content on YouTube. - Ivaan Pitua; Raafidha Raizudheen; Amelia Margaret Namiiro; Lorraine Apili; Felix Bongomin (PLoS Neglected Tropical Diseases)
Background Mycetoma is a fungal neglected tropical disease. Accurate dissemination of information is critical in endemic areas. YouTube, a popular platform for health information, hosts numerous videos on mycetoma, but the quality and reliability of these videos remain largely unassessed. Methods We used modified DISCERN and Global Quality Score (GQS) for reliability and quality respectively. Video duration, views, likes, and comments were recorded. Spearman's rank correlation and Mann-Whitney U tests were used to identify correlations between metrices and quality scores. Results We included 73 mycetoma-related YouTube videos were analyzed, the median GQS score was 4.00 ((IQR = 3.33-4.00), indicating generally high-quality content, while the median mDISCERN score was 3.00 (IQR = 3.00-3.00) reflecting moderate reliability. Videos produced by professionals had significantly higher scores compared to those from consumer-generated content (p < 0.001). A significantly positive correlation was observed between video duration and both GQS (r = 0.417, p < 0.001) and mDISCERN (r = 0.343, p = 0.003). However, views, likes and comments did not significantly correlate with video quality. Additionally, videos longer in duration (p < 0.001) and older in upload date (p = 0.014) had higher quality scores. Conclusions The study shows that mycetoma-related videos on YouTube are generally of high quality, with moderate reliability. This emphasizes the need for expert involvement in content creation and efforts to improve health information online.